Green policy under the competitive electricity market: An agent-based model simulation in Shanghai. (1st December 2021) - Zhou, Yang; Shi, Zhengyu; Wu, Libo
Abstract: China has begun a new round of electricity market reform since 2015, aiming to transform the regulated form into a competitive one. Since the generation cost of clean energy is still relatively high compared to coal-fired power plants, the major source of the energy sector in China, the environmental outcomes from market reform would remain uncertain. Therefore, green policies play a critical role during the process of reform and hence would determine whether China can achieve the goal of carbon-neutral in 2060. In light of these concerns, this paper performed a simulation study based on the agent-based model (ABM) to analyze the market performance and environmental conditions after reform. Our results demonstrate that given current cost disadvantages, the market share will flow to coal-fired power plants in the competitive electricity market without the support of green policies, resulting in the increase of CO2, NOX, SO2, and smoke emissions by 4.85 %, −1.7 %, 6.48 %, and 6.86 %. Further scenario analysis shows that to improve such environmental outcomes, policies should focus on pushing the replacement of coal-fired energy, either by renewable or gas energy. The simulation results of green policy scenarios demonstrate significant co-benefits, that carbon and other pollution emissions will decrease simultaneously. Despite the environmental gain from green policies, results of the policy efficiency analysis indicates that the FIT on renewable energy is the least effective, while pollution tax turns to be the most effective. Our results imply that green policies should be well considered when constructing the competitive electricity market in China, to effectively achieve both the national carbon-neutral and local environmental goals. Highlights: Green policies should be well designed during electricity market reform. The environmental condition may get worse without green policies. Green policies in the electricity market in China should focus on the replacement of coal-fired energy. Green policies demonstrate significant environmental co-benefits on carbon and pollution control in the energy sector. Pollution tax in the electricity market shows the highest efficiency.